Information System Design at FGH Stores with Unified Modelling Language - Djarot Hindarto; Mochamad Hariadi (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
This project aims to develop and execute a proficient information system at FGH Stores, to enhance sales performance and improve customer satisfaction. This study centers on incorporating information technology into routine business activities, intending to devise strategies that facilitate seamless consumer interactions and aid store management in effectively handling inventory and customer data. The research process includes the examination of business needs, the formulation of system architecture, the creation of user interfaces that prioritize ease of use, and the integration of databases. The resultant information system facilitates consumer registration as members, reduces browsing of product catalogs, and enables efficient execution of purchases. Furthermore, implementing shop management systems enables enhanced inventory monitoring, efficient customer data management, and improved responsiveness to consumer requests. This study assesses the effects of information systems on enhancing sales and operational efficiency by conducting data collection and analysis before and after deployment. The findings indicated that implementing information systems effectively enhanced the efficiency of the sales process and improved the customer experience, yielding substantial advantages for the growth of retail establishments. This study offers valuable insights into the possible utilization of information technology within the retail industry while also contributing to the comprehension of the favorable effects that information systems integration may have on corporate expansion and customer satisfaction.